Knowledge management capabilities and organizational performance in a North African context: The mediating role of business model innovation - Ghanem, Insaf Ben; Chaabouni, Amel (Edelweiss Applied Science and Technology, 2026)
This study investigates the impact of knowledge management capabilities (KMC) on organizational performance, emphasizing the mediating role of business model innovation (BMI). Drawing on the perspective of KMC, the research conceptualizes knowledge infrastructure as comprising technology, structure, and culture, and knowledge process architecture as encompassing acquisition, conversion, application, and protection. Utilizing quantitative methods, this research gathered data through questionnaires from a sample of 391 managers working in banks and insurance companies in Tunisia, a North African country, and analyzed the data using Amos 10. The data were analyzed using Amos 10 with the maximum likelihood estimation method (LISREL). The results demonstrate that both knowledge management capabilities and business model innovation significantly enhance organizational performance, particularly through organizational structure, technology, knowledge conversion, application, and protection. Furthermore, the findings confirm that BMI mediates the relationship between knowledge management capabilities and organizational performance. The study extends an existing pool of knowledge regarding the large-scale influence of innovation on firm performance. It also provides valuable insights for financial institutions seeking to improve their performance by fostering innovation activities through effective utilization of BMI.